Mewujudkan generasi emas 2045: upaya peningkatan akses pendidikan di wilayah terpencil - fitriana, saskia fitriana saskia (Maliki Interdisciplinary Journal, 2025)
Equitable education is one of the key factors in realizing the Golden Generation 2045, a generation of superior quality. However, limited access to education in remote areas is still a major challenge for equalizing the quality of human resources in Indonesia, such as limited infrastructure, lack of educators, low access to technology, and lack of sustainable policy support. This article discusses various efforts that can be made to improve access to education in remote areas, ranging from the development and improvement of school infrastructure, the utilization of digital technology, improving the competence of educators, to the synergy between the government, the community and the private sector. With the right and sustainable strategies, equitable education in remote areas can be realized, so that every Indonesian child has the same opportunity to develop and contribute to building the nation towards a resilient, superior, highly competitive Golden Indonesia 2045, has a strong personality, national spirit, and is able to understand science and technology in order to compete globally on the basis of formal, informal and non-formal education.